Measurements of a confined circular jet - Tong, Xu Le (2014)
In this final year project, the flow characteristics of an air jet issuing from a vertical circular nozzle of diameter 22mm into a confined chamber are being studied. Hot wire anemometry technique was used in the experiments for measurements. Hot wire measurements of mean and root mean square velocities were made in the streamwise direction, at distances up to 20 nozzle diameters downstream of the jet flow. All experiments were carried out at Reynolds number of 15433. The experiments were carried out in two phases, first by using a single hot wire probe and thereafter a cross-wire probe. The results showed that the mean velocity profiles achieved approximate self-preservation after the end of the potential core. However, the self-similarity of root mean square velocity profiles were not established at x/d = 5, where x is the streamwise direction of the flow and d is the diameter of the jet nozzle. Decay rate of the confined circular jet was found to be 0.1597, with laminar initial conditions. The spreading rate of the jet was found to be 0.1132 and it can be deduced from comparison of past results that a lower decay rate results in a higher spreading rate. The Reynolds shear stress obtained did not indicate that the flow was self-preserving. The present work does not include mean and root mean square temperature measurement of the flow as cold wire technique was not used.